Effectiveness of Personalized Learning with Interactive Flipbook Media in Learning Sequences and Series: A Systematic Literature Review - Iwan Iwan; Khaerudin Khaerudin; Cecep Kustandi; Imam Fitri Rahmadi (FKIP - Universitas Riau, 2026)
Mathematics learning, particularly in sequences and series, faces epistemological, ontogenic, and didactic obstacles that have not been optimally addressed through conventional approaches. This study aims to conduct a systematic literature review on the effectiveness of personalized learning approaches supported by interactive flipbook media in learning sequences and series. The study employed the PRISMA method on SCOPUS and SINTA databases for the period 2020-2024. From 64,307 identified articles, 25 articles met the inclusion criteria and were assessed for quality using the CASP-JBI (Critical Appraisal Skills Programme-Joanna Briggs Institute) instrument. The assessment results showed that 25 articles had scores greater than or equal to 7 (high quality), which were then analyzed using thematic content analysis. Findings indicate that effective learning designs must consider learning obstacles through stages of initial situation, exploration, formulation, application, and remediation. The personalized learning approach with interactive flipbooks proved more effective than conventional learning in improving conceptual understanding, learning motivation, and students' problem-solving abilities. Flipbook media supports personalized learning through multimedia integration, interactive elements, and flexible accessibility. The research provides recommendations for developing flipbook media that integrates various learning styles and effective learning approaches such as RME and Discovery Learning.